2017
DOI: 10.1056/nejmoa1616011
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide and Renal Outcomes in Type 2 Diabetes

Abstract: This prespecified secondary analysis shows that, when added to usual care, liraglutide resulted in lower rates of the development and progression of diabetic kidney disease than placebo. (Funded by Novo Nordisk and the National Institutes of Health; LEADER ClinicalTrials.gov number, NCT01179048 .).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
678
1
32

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 985 publications
(765 citation statements)
references
References 31 publications
16
678
1
32
Order By: Relevance
“…This benefit was driven by a 26% reduction in new-onset macroalbuminuria (HR, 0.74; 95% CI, 0.60 to 0.91; P50.004). The rate of decline in eGFR during the study was also modestly lower in participants receiving liraglutide compared with the placebo group (27.4 versus 27.8 ml/min per 1.73 m 2 over 36 months; P50.01), especially in participants with stage 3 or 4 CKD at baseline (5). However, the number of participants who experienced a persistent doubling of serum creatinine level and an eGFR#45 ml/min per 1.73 m 2 was unaffected (HR, 0.89; 95% CI, 0.67 to 1.19; P50.43), and no changes were observed in the incidence of ESRD (5).…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…This benefit was driven by a 26% reduction in new-onset macroalbuminuria (HR, 0.74; 95% CI, 0.60 to 0.91; P50.004). The rate of decline in eGFR during the study was also modestly lower in participants receiving liraglutide compared with the placebo group (27.4 versus 27.8 ml/min per 1.73 m 2 over 36 months; P50.01), especially in participants with stage 3 or 4 CKD at baseline (5). However, the number of participants who experienced a persistent doubling of serum creatinine level and an eGFR#45 ml/min per 1.73 m 2 was unaffected (HR, 0.89; 95% CI, 0.67 to 1.19; P50.43), and no changes were observed in the incidence of ESRD (5).…”
mentioning
confidence: 89%
“…Reductions in insulin, body weight, and BP may also have benefits in the kidney. Nonetheless, sensitivity analysis from the LEADER Trial suggests that the effects of liraglutide were partly independent of improvement in glycemic control (20.4% hemoglobin A1c) and body weight (22.3 kg) between the two study arms (5). Equally, the clear reduction in albuminuria in the AWARD-7 Trial, in which glycemic equipoise was achieved (9), seems consistent with glucose-independent actions on CKD in type 2 diabetes.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…So far, only liraglutide has shown renal benefit in a large outcome trial. In a secondary analysis of the LEADER trial (20), a lower proportion of liraglutide treated patients displayed progression to macroalbuminuria, making up the major part of the combined renal endpoint which occurred in 15 versus 19 patients per 1,000 patient-years of observation in the liraglutide and the placebo group, respectively.…”
Section: Other Antidiabetic Treatment and Albuminuriamentioning
confidence: 99%
“…The Liraglutide and Renal Outcomes in Diabetes trial reported on the composite renal outcome occurring in fewer participants in the liraglutide group than in the placebo group (HR = 0.78; 95% CI 0.67–0.92). This result was driven primarily by the new onset of persistent macroalbuminuria, which occurred in fewer participants in the liraglutide group than in the placebo group (161 vs. 215 patients; HR = 0.74; 95% CI 0.60–0.91) [18]. A recent post hoc analysis of the Liraglutide Effect and Action in Diabetes (LEADER) trial reported that in patients with eGFR < 60 mL/min/1.73 m 2 the risk reduction for the primary composite cardiovascular outcome with liraglutide was greater (HR = 0.69; 95% CI 0.57–0.85) versus those with eGFR ≥60 mL/min/1.73 m 2 (HR = 0.94; 95% CI 0.83–1.07) [19].…”
Section: Updates From Cardiovascular and Renal Outcomes Trials In 2018mentioning
confidence: 99%